A CDA Al Gore's lecture at Nobel Peace Prize Award 2007 - Hoàng, Nguyệt Anh (ĐHNN, 2017)
The analysis of the lecture reveals how Al Gore created and reinforced his power and ideology by virtue of linguistic features: the speaker's power is expressed explicitly in the discourse via the popular use of modality most of which convey direct request (...)